Factors contributing to a reluctance of clinical facilitators at a private nursing education institution in Gauteng to fail student nurses who are not competent - Willemse, Sonia (My University, 2016)
The past decade has seen an abundance of research related to the assessment of nursing students in clinical practice. Assessment serves several purposes: to regulate entry into the profession, as a quality control mechanism for the profession, to motivate students and to support teaching and learning. Agreement in the literature exists that assessment of clinical competency is complex, although necessary to safeguard the public and uphold the professional image of the nursing profession. Clinical facilitators have a professional responsibility to act as the “gatekeepers” of the nursing profession preventing borderline and unsafe students from being entered onto the professional register. Evidence from the literature and anecdotal evidence confirmed that clinical facilitators are not effective “gatekeepers” to the profession. Anecdotal evidence suggested that students who are not competent during clinical assessments are frequently graded as competent. The aim of this study was to establish whether clinical facilitators are reluctant to fail student nurses who are not competent and to identify and describe factors contributing to their reluctance to fail student nurses who are not competent. Research methodology A qualitative, exploratory, descriptive and cross-sectional contextual research design was used. The population included the clinical facilitators employed at the clinical placement facilities where the students are placed for their clinical practicum or at the NEI itself. Focus group discussions and semi-structured interviews were used to collect data. The discussions and interviews were recorded and transcribed verbatim. The transcribed data was analysed and coded using “Tesch’s Eight Steps in the Coding Process”. Main findings The study revealed that clinical facilitators were, in certain circumstances, reluctant to fail student nurses who are not competent. Four categories emerged from the data viz. student related factors, programme requirements, the assessment process and facilitator related factors. Recommendations The Nursing Education Institution should review current assessment practices if assessments and should implement mentorship and training and development programmes to assist clinical facilitators to develop competency in their role as assessors. A review should be undertaken of the moderator’s role in assessments, and policies regarding assessment and moderation policies to mitigate the risk of “failure to fail”. There should be greater cooperation between the NEI and the clinical placement facility to optimize student learning and assessments. Further research should be directed at supporting teachers and learners regarding effective assessment. Conclusion Assessing students in clinical practice is complex and identifying unsafe students in clinical practice is not as straight forward as it may seem. “Failure to fail” is a multifaceted problem that needs to be addressed across all faculties in health sciences to ensure that graduates from nursing programmes have met specific competence criteria and are “fit to practice” safely and competently.
Master of Science in Nursing August 2016